Does Cooperative Script affect the students' reading comprehension? - Wahyuningtias, Merisa; Khoiriyah, Khoiriyah; Sulistyani, Sulistyani (The Proceedings of English Language Teaching, Literature, and Translation (ELTLT), 2023)
This study is intended to find out the effect of using Cooperative Script technique on the students' reading comprehension of the first grade at SMA Negeri 4 Kediri. The research approach used in this study was quantitative with a pre-experimental technique. Technique of collecting data used was pre-test, treatment, post-test. Pre-test which instrument to know the reading comprehension of the students before being taught by Cooperative Script techniques was implemented before treatment which consists of several steps, while post-test was applied after treatment. The participants were 34 students. Data analysis used was T-test counted with SPSS version 23. The result showed that the score of post-test was higher than pre-test with mean score of pre-test was 58.82 and mean score of the post-test was 81.18. Thus, it can be said that Cooperative Script had significant effect on the students' reading comprehension of the first grade at SMAN 4 Kediri.